2019
DOI: 10.1089/jpm.2018.0082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists Providing Palliative Care Services: Demonstrating a Positive Return on Investment

Abstract: Objective: To establish a return on investment (ROI) for a pharmacist position on a hospital-based palliative care (PC) team. Background: Utilizing a pharmacist to provide PC services is often overlooked as a solution to physician shortages. Integration of a pharmacist into PC teams yields a favorable ROI. Methods: A 16-month retrospective review comparing PC patients at two hospitals with consultative PC teams. The PC teams at the two facilities had identical full-time equivalent team members, except for a PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…These contributions align with the American Society of Health‐Systems Pharmacists Guidelines on the Pharmacist's Role in Palliative and Hospice Care 16 . A retrospective review showed that a palliative care pharmacist's participation in the PCT resulted in a return on investment of 1.2 to 2.9 million dollars over a 16‐month timeframe 17 …”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These contributions align with the American Society of Health‐Systems Pharmacists Guidelines on the Pharmacist's Role in Palliative and Hospice Care 16 . A retrospective review showed that a palliative care pharmacist's participation in the PCT resulted in a return on investment of 1.2 to 2.9 million dollars over a 16‐month timeframe 17 …”
Section: Introductionmentioning
confidence: 73%
“…16 A retrospective review showed that a palliative care pharmacist's participation in the PCT resulted in a return on investment of 1.2 to 2.9 million dollars over a 16-month timeframe. 17 Polypharmacy is often defined as routinely taking five or more medications. 18 Polypharmacy has become increasingly common, with one cross-sectional analysis finding that the proportion of adults dispensed five or more medications has doubled between 1995 and 2010.…”
mentioning
confidence: 99%
“…These notions were supported by a nurse from the Office of Nursing Affairs of the Veterans Affairs, stating that OPs were already extending capacity by managing oral oncology clinics. Another participant stated that incorporating pharmacists into the palliative care team was a cost-effective strategy for increased patient services [17].…”
Section: Discussionmentioning
confidence: 99%
“…They can provide comprehensive drug therapy, including the observation of pharmacokinetic parameters, timely adjustment of medication regimens, review of prescriptions and working as a part of a multidiscipline, because they have more contact with inpatients and grasp more information [35]. Furthermore, clinical pharmacists can provide medication counseling for patients and their families [36], so clinical pharmacists may save more PE for inpatients. Physicians may increase hospital outpatient PE.…”
Section: Discussionmentioning
confidence: 99%